2020
DOI: 10.1063/5.0006077
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in antiferromagnets

Abstract: Due to the advent of antiferromagnetic (AF) spintronics there is a burgeoning interest in AF materials for a wide range of potential and actual applications. Generally, AFs are characterized via the ordering at the Néel temperature (TN) but, to have a stable AF configuration, it is necessary that the material have a sufficient level of anisotropy so as to maintain the orientation of the given magnetic state fixed in one direction. Unlike the case for ferromagnets there is little established data on the anisotr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…Through XMCD and magnetometry, it was found that the core of each shape is well described by bulk . As an antiferromagnet, the absence of a net magnetic moment in the core precludes the possibility of shape anisotropy 38 . Thus, any increase in the effective anisotropy comes from the different surface environments such as steps, kinks, and exchange interactions 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Through XMCD and magnetometry, it was found that the core of each shape is well described by bulk . As an antiferromagnet, the absence of a net magnetic moment in the core precludes the possibility of shape anisotropy 38 . Thus, any increase in the effective anisotropy comes from the different surface environments such as steps, kinks, and exchange interactions 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…34 2D CrBO 3 with room-temperature magnetism is expected to replace the MnPS 3 as the magnon transport medium in a magnonic transport-based device 11 but may not be appropriate in the read-head devices due to its low anisotropy. 35 Interestingly, the MAE of 2D VBO 3 and MnBO 3 are 1953 and 896 μeV/TM, respectively, which are larger than that of the antiferromagnetic FeAs-III monolayer (820 μeV/TM) 14 and ferromagnetic CrI 3 monolayer (685 μeV/TM) 36 but smaller than that of ferromagnetic α-FeB 3 (4130 μeV/TM). 37 Two-dimensional (2D) VBO 3 and MnBO 3 display high thermal stability due to their very high anisotropy and are promising candidates for read-head devices below room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…37 Two-dimensional (2D) VBO 3 and MnBO 3 display high thermal stability due to their very high anisotropy and are promising candidates for read-head devices below room temperature. 35 To develop practical spintronic devices working in the ambient environment, the Neél temperature of 2D antiferromagnetic materials should be higher than room temperature. As shown in Figure S2b, there are two sets of sublattices, A-sublattice and B-sublattice, in the nAFM state.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the logic functions of present magnetic devices are mostly realized by the trivial existence/absence states of magnetic textures [31][32][33][34] . A promising candidate with intrinsic reprogrammability is the 90 • domain wall with multiple variants in cubic anisotropic materials including RbMnF 3 [35][36][37] , NiO [38][39][40][41] , Mn 3 Pt 42,43 , Heusler alloys 44,45 , etc. The 90 • domain wall has been studied both experimentally and theoretically, including spin wave guiding 17 and refraction 46 , and the domain wall motion driven by electric current 14 or spin-orbit field 47,48 .…”
mentioning
confidence: 99%